Muscle-Sparing Skin-Reducing Breast Reconstruction with Pre-Pectoral Implants in Breast Cancer Patients: Long-Term Assessment of Patients' Satisfaction and Quality of Life. Issue 4 (3rd April 2022) - Domenici, Lavinia; Caputo, Glenda Giorgia; Losco, Luigi; Di Taranto, Giuseppe; Lo Torto, Federico; Pierazzi, Diletta Maria; Governa, Maurizio; Benedetti Panici, Pierluigi; Ribuffo, Diego; Cigna, Emanuele
Abstract: Introduction: Breast cancer is the most frequently diagnosed tumor in women; globally, it accounts 23% of all cancer deaths. Breast reconstruction after oncologic surgery has become crucial to enhance patients' quality of life and alleviate the psychological distress related to the disease. The aim of this study was to assess quality of life and esthetic satisfaction of breast cancer patients undergoing muscle-sparing skin-reducing breast reconstruction (MS-SR) with pre-pectoral implants. Methods: Sixty-three patients who met definite oncological and reconstructive criteria were enrolled in the study. Specific questionnaires (EORTC QLQ-C30, QLQ-BR23) were administered preoperatively, 1, and 12 months after MS-SR breast reconstruction to evaluate patients' QoL. Satisfaction with procedure and related Quality of Life were assessed through BREAST-Q questionnaire preoperatively and 12 months after surgery. Results: Sixty-three breast cancer patients underwent MS-SR. Seventy-eight procedures were carried out; in 15 patients a bilateral reconstruction was performed. One month after surgery, both EORTC QLQ-C30 and QLQ-BR23 average scores demonstrated a slight drop since preoperative values, but a significant improvement in QoL was documented 12 months after BR ( p < 0.05). BREAST-Q test showed significant psychophysical and esthetic satisfaction 12 months postoperatively. Conclusions: Muscle-sparing skin-reducing breast reconstruction is an established and reliable technique. EORTC QLQ-C30, QLQ-BR23 and BREAST-Q scores showed an improvement of patients' QoL and esthetic satisfaction. Reduction of pain and other surgery-related symptoms are cornerstones of patient well-being. Both physicians and patients should build a thorough awareness of the silver lining of muscle-sparing skin-reducing breast reconstruction based on the high safety profile and highly satisfactory patient-reported results.